A Phantom Verb "Yuttan" in Biblical Hebrew - Aikhler, Raʿanan 1980- (2023)
The verb נתן "to give" is pointed as hophal eight times in the Bible. The scholarly consensus is that these occurrences were originally intended as qal-passive, and that there was no hophal נתן in original Biblical Hebrew. It is argued here that there was neither hophal nor qal-passive נתן in original Biblical Hebrew: these occurrences were originally intended as qal, their subjects were indefinite, and they were intuitively revocalized as hophal when the third-person singular indefinite subject fell out of use in Hebrew.